DESIGNING (ATELIER LA) FASHION CENTER WITH A MODERN ARCHITECTURAL APPROACH ON JALAN SOEKARNO HATTA LAMONGAN - Alfina Nuril Husniyah; Mimin Aminah Yusuf; Dhiah Agustina Qahar; Afin Ulul Azmi (DEARSIP : Journal of Architecture and Civil, 2025)
The fashion industry in Lamongan Regency shows rapid development, characterized by high public interest and the organization of various fashion events. However, promotional activities and fashion shows carried out by the Lamongan Regency Government are still carried out in less representative locations, such as on public roads that cause traffic disruptions, or in Sports Buildings (GOR). This condition highlights the need for adequate facilities. Therefore, this research aims to design a Fashion Center that can function as a forum for collaboration, education, training, and commercial activities to support the growth of the local clothing industry. The design applies the Modern Architectural Approach to integrate functional and aesthetic elements, creating a timeless and attractive space. The methods used are the flow chart design methodology from Goldschmidt (Analysis and Synthesis) and the Cinegram analysis method from Bernard Tschumi, which includes programmatic, footprint, and design approach analysis. The design results are expected to provide architectural design solutions that are functional, aesthetic, and adaptive to the needs of the fashion industry, while contributing positively to the local economy.